The long‐term cardiovascular impact of hypertension in pregnancy – A missed opportunity. (18th March 2021) - Davis, Gregory K.; Henry, Amanda; Arnott, Clare; Brown, Mark A.
Abstract : Women who have had hypertension in pregnancy, both pre‐eclampsia and gestational hypertension, have a two‐ to three‐fold increased risk of cardiovascular disease later in life. It is unclear whether this is an unmasking of latent risk, the result of damage to the vascular tree during pregnancy, or both. Irrespective of the underlying pathophysiology, these women are uniquely identified sufficiently early in their lives for lifestyle interventions, if adopted, to improve their long‐term health. Currently, follow‐up of these women is inadequate and implementation of a coordinated follow‐up program, and further research into how best to provide it, is urgently needed.